Innovative Marketing Strategies for Enhancing Neighbourhood Conversational Commerce - Andriyansah; Maria, Maya; Riana, Kurnia Endah; Pujiastuti, Sri Lestari; Yolanda, Ledy (Yayasan Sinergi Kawula Muda, 2025)
Conversational commerce (c-commerce) leveraging messaging platforms like WhatsApp presents new opportunities for local neighbourhood engagement in service-oriented markets. Aim: This study investigates how WhatsApp-based conversational agents influence consumer buying behaviour within a local workplace context, introducing the concept of Conversational Commerce of Neighbourhood. Methods: Employing a user-centred design approach, we collected quantitative data from 110 active employees at the Faculty of Economics and Business, Universitas Terbuka, via surveys and observations of a WhatsApp prototype, and conducted qualitative interviews to triangulate findings. Results: Quantitative results show that 73% of respondents reported higher satisfaction with WhatsApp-based local communications, and 65% indicated a higher likelihood of purchasing after personalised interactions; however, 25% expressed concerns about data privacy. Regression analysis indicates significant positive effects of WhatsApp usage on customer satisfaction (p < 0.001), with interaction frequency (p < 0.01) and tailored user satisfaction having substantial influence (coefficient for user satisfaction = 0.85). Qualitative insights highlight the value of personal touch, faster responses, and stronger branding perception in fostering loyalty. Conclusions: When designed with local cultural contexts and transparent data practices, neighbourhood-focused c-commerce via WhatsApp can enhance consumer engagement and purchasing outcomes, offering practical guidance for local businesses and contributing to the theoretical understanding of e-commerce and human–computer interaction in local settings.